Experimental Study on Shear Characteristics of Coal Samples in Different Water-Bearing States - Yang Wu; Lujun Wang; Baoyang Wu; Ze Xia (Advances in Civil Engineering)
During the establishment of the coal mine goaf reservoir, the strength of the coal pillar dam was weakened by various water–rock interactions triggered by water movement. To explore the influence of the water-bearing state on the shear characteristics of coal pillar dams, the 2–2 coal seam of Shangwan Coal Mine in the Shendong Mining area was taken as the research object and was prepared to coal samples with different moisture contents and different drying-saturation cycles, and the variable angle shear test of coal samples was carried out. The law of water absorption of coal samples under natural and pressurized conditions is obtained. The research results show that the shear characteristics of coal samples change significantly under the action of water, with the increase of moisture content and drying-saturation cycles, the lower the shear strength of coal samples is, the larger the peak shear strain is, and the cohesion and internal friction angle of coal samples decrease linearly. According to the relationship between cohesion, internal friction angle, moisture content, and drying-saturation cycle times, the Mohr–Coulomb model of coal samples considering moisture content and immersion times is established, which contributes to the load-bearing capacity estimation of water-bearing coal mass. Additionally, scanning electron microscope analysis revealed significant changes in the microstructure of coal samples under different moisture states: as the moisture content and dry-saturation cycles increase, the microstructure of the coal samples gradually transforms from orderly and compact to disordered and murky, elucidating the mechanism by which moisture weakens the mechanical properties of the coal samples. The research results provide a useful reference for engineering problems related to the stability evaluation of coal bodies involving the repeated erosion effect of water.